2011
DOI: 10.1085/jgp.201110705
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the channel function of a degraded ABC transporter, CFTR (ABCC7)

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is a member of the ATP-binding cassette (ABC) transporter superfamily, but little is known about how this ion channel that harbors an uninterrupted ion permeation pathway evolves from a transporter that works by alternately exposing its substrate conduit to the two sides of the membrane. Here, we assessed reactivity of intracellularly applied thiol-specific probes with cysteine residues substituted into the 12th transmembrane segment (TM12) of CFTR. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
131
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(159 citation statements)
references
References 52 publications
25
131
3
Order By: Relevance
“…Yet several residues on TM12 are known to be exposed to a more hydrophobic environment in closed channels, namely residues 1141, 1142, 1145, 1147 and 1150. 55 In accord with this observation, residues 1141, 1145 and 1150 have lower predicted averaged %SASA values in the MDFF simulations than in both initial models. Residue 1142 has a lower predicted %SASA only in the MDFF simulations initiated from the Dalton model, whereas residue 1147 has higher %SASA in MDFF simulations initiated from both models, but still lower than the cutoff value of 20%.…”
Section: Agreement With Experimentally Determined Solvent Accessible supporting
confidence: 60%
“…Yet several residues on TM12 are known to be exposed to a more hydrophobic environment in closed channels, namely residues 1141, 1142, 1145, 1147 and 1150. 55 In accord with this observation, residues 1141, 1145 and 1150 have lower predicted averaged %SASA values in the MDFF simulations than in both initial models. Residue 1142 has a lower predicted %SASA only in the MDFF simulations initiated from the Dalton model, whereas residue 1147 has higher %SASA in MDFF simulations initiated from both models, but still lower than the cutoff value of 20%.…”
Section: Agreement With Experimentally Determined Solvent Accessible supporting
confidence: 60%
“…Kirk 2008;Jordan et al 2008). This proposition is supported by a very recent report providing strong evidence that the gate of CFTR is indeed located more to the extracellular part of the pore (Bai et al 2011;but cf. El Hiani and Linsdell 2010;Wang and Linsdell 2012).…”
supporting
confidence: 55%
“…TMs 5, 11, and 12 also have been argued to contribute to the pore based on mutagenesis and cysteine scanning results (Zhang et al 2000a,b;Fatehi and Linsdell 2009). Recent results from systematic cysteine scanning studies not only suggest that TM12 assumes an a-helical secondary structure, but also support the idea that TM12 is part of the pore-forming domain (Bai et al 2011;cf. Qian et al 2011).…”
Section: Pore-lining Tmsmentioning
confidence: 73%
See 1 more Smart Citation
“…Based on functional data and homology models, CFTR has been predicted to contain five functional domains: two membranespanning domains (MSDs), each including six transmembrane (TM) helices; two nucleotide binding domains (NBD1 and NBD2); and a unique regulatory (R) domain, which carries multiple protein kinase A (PKA) consensus phosphorylation sites and is unique to CFTR in the ABC superfamily (1)(2)(3)(4)(5)(6). Functional studies from multiple groups have suggested that TM6 plays an essential role and TM12 contributes less to anion conduction and permeation properties in the CFTR channel pore (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%